Pengaruh Murottal Terhadap Tingkat Kecemasan Pada Ibu Bersalin Kala I Di PMB Eka Susanti - Adianti, Fera; Kusumadewi, Rita Riyanti; Winarni, Winarni; Widiyati, Rina Sri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Anxiety can be reduced using relaxation and ditraction therapy, one of the efforts to reduce anxiety in mothers giving birth is using Murottal therapy, namely a recording of the sound of the Al-Quran sung by a qori' or Al-Quran reader. The sound of chanting verses from the Al-quran activates endorphin hormones and can stimulate delta waves, making the listener calm, peaceful and comfortable. This research is to determine the effect of murottal before and after administration on reducing anxiety levels in mothers giving birth. This research uses Pre Experimental with a One Group Pretest Posttest Design research design. The sample in this study was 27 respondents with Purposive Sampling. Bases on analysis showed that before murottal therapy was carried out, the majority were at a moderate level of anxiety, 16 people (59.3%). After murottal therapy, the majority of respondents were at a mild level of anxiety, 18 people (66.7%). Statistical analysis used the Wilcoxon test with a p-value of 0.000 (<0.005). There is an effect on reducing maternal anxiety in the first stage of labor after being given murottal therapy.